Reimbursement Legislations and Decision Making for Orphan Drugs in Central and Eastern European Countries - Malinowski, Krzysztof Piotr; Kawalec, Paweł; Trąbka, Wojciech; Czech, Marcin; Petrova, Guenka; Manova, Manoela; Savova, Alexandra; Draganić, Pero; Vostalová, Lenka; Slabý, Juraj; Männik, Agnes; Márky, Kristóf; et al. (Frontiers in Pharmacology, 2019)
Background: Reimbursement policies influence access of patients to orphan drugs in the European countries. Objectives: To provide a comprehensive description of orphan drug reimbursement policies and to assess reimbursement decision-making process in the EU-CEE countries as well as the impact of the type of approval and disease on reimbursement decisions. Methods: For each drug, the information regarding conditional approval or approval under exceptional circumstances was obtained from the EMA website. The reimbursement status for analysed drugs was collected in a questionnaire survey performed in a group of experts in reimbursement policy. The agreement between countries was assessed using the κ coefficient, nominal variables tests were compared using the χ2 test or the Fisher exact test. The impact of the EMA’s conditional approval and approval under exceptional circumstances was assessed using logistic regression and presented as an odds ratio (OR). Results: The analysis revealed that most orphan drugs were authorised for the treatment of oncological or metabolic diseases (36 drugs [38%] and 22 drugs [23%], respectively). The shares of reimbursed orphan drugs varied significantly (p=0.0031) from 6.3% in Latvia to 27.4% in Poland. No correlation (r=0.02; p=0.9583) with GDP per capita was observed. The highest agreement in reimbursement decisions was observed between Estonia and Lithuania, and the lowest – between Estonia and Latvia, with kappa of 0.69 and 0.11, respectively. Significant impact of the type of approval and reimbursement status was observed for Czech Republic, Lithuania and Slovakia where conditional approval and exceptional circumstances negatively influenced reimbursement decision. Type of disease has significant influence on reimbursement decision in 4 out of 10 analysed countries with significant outweigh of positive decisions for oncological diseases. Conclusions: In considered countries specific regulations on reimbursement of orphan drugs are valid but in Lithuania and Romania no formal HTA process was employed; in case of some countries higher ICER values for orphans are used. The share of reimbursed orphan drugs varied significantly across the countries, but it was not associated with GDP per capita.